2022
DOI: 10.4193/rhin21.355
|View full text |Cite
|
Sign up to set email alerts
|

As-needed intranasal corticosteroid spray for allergic rhinitis: a systematic review and meta-analysis

Abstract: Background: As-needed intranasal corticosteroid spray (INCS) is commonly used by patients with allergic rhinitis (AR) who have suboptimal symptom control. This systematic review aimed to assess the effectiveness of as-needed INCS for treating AR. Methodology: Systematic searches for randomized controlled trials studying the effects of as-needed INCS compared to regular INCS, as-needed antihistamine, or placebo were performed. Primary outcomes were total nasal symptom score (TNSS) and disease-specific quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The promise of PRN therapy in managing AR is supported by recent updates to AR guidelines 1 and recent clinical studies. 19 , 28 , 29 , 30 , 31 , 32 Additional descriptive analyses have also been carried out. 31 Two analyses by the Mobile Airways Sentinel Network (MASK) 28 , 29 , 30 were designed to utilise data from more than 9000 users from 22 countries, confirming results from a pilot study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The promise of PRN therapy in managing AR is supported by recent updates to AR guidelines 1 and recent clinical studies. 19 , 28 , 29 , 30 , 31 , 32 Additional descriptive analyses have also been carried out. 31 Two analyses by the Mobile Airways Sentinel Network (MASK) 28 , 29 , 30 were designed to utilise data from more than 9000 users from 22 countries, confirming results from a pilot study.…”
Section: Discussionmentioning
confidence: 99%
“… 1 A recent systematic review was designed to assess the effectiveness of PRN INCS for treating AR. 32 Eight studies involving a total of 882 participants met the criteria. 19 , 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 While regular INCS use improved TNSS and disease-specific quality of life more than PRN INCS, PRN INCS improved TNSS more than PRN antihistamine and placebo.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis concludes that based on their results, INCs are not associated with a significant increased risk of elevating the intraocular pressure (relative risk 2.24 [95% CI: 0.68–7.34, 494 studies]) or developing cataracts (absolute increased incidence 0.02% [95% CI: −0.3% to 0.4%, 494 studies]). An association with the risk of occurrence of glaucoma cannot be ruled out 13 . The association between INCs and the occurrence of chorioretinopathy is rare 39 .…”
Section: Efficacy and Safety Of Intranasal Corticosteroidsmentioning
confidence: 99%
“… 9 , 10 For mild‐to‐moderate AR symptoms, INC therapy is not recommended, although studies have suggested that INCs may be effective as as‐needed therapy for mild AR symptoms, compared with placebo and antihistamines. 11 , 12 , 13 Hoang et al 13 emphasize that regular use of INCs provides greater benefits than the as‐needed therapy in total nasal symptoms score and disease‐specific QoL.…”
Section: Efficacy and Safety Of Intranasal Corticosteroidsmentioning
confidence: 99%
See 1 more Smart Citation